If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -18 = y Reorder the terms: -18 + 5x = y Solving -18 + 5x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 5x = 18 + y Combine like terms: -18 + 18 = 0 0 + 5x = 18 + y 5x = 18 + y Divide each side by '5'. x = 3.6 + 0.2y Simplifying x = 3.6 + 0.2y
| 5y^2-13y-28= | | 1x-1=5x-4x-4+25 | | -99/x=2 | | 3x+19=56 | | V=(24-2x)(18-2x)x | | -3x+14=-7 | | 9x+7y=19.7 | | 6r^4/r^7 | | 2e^3x-1=e^2x+1 | | 3(3x+5y)-9x-7y=3(19.825)-19.7 | | 2x(x-3)=8(x-3) | | X^8/x^9 | | -8-3=10x+3-9x | | 11x-9y-10= | | a*3+5=12 | | 4x(3x^3y^4)= | | I=F-IR | | 2x^2-20x-48= | | 5x+6x-3=21 | | F-IR=I | | 7/9-3/18 | | F=i+ir | | x^2+3x-2012=0 | | (w)(w+7)=0 | | x-18sqrtx+80=0 | | I=f-1ir | | (4x^2-x)= | | (y-5)2=100 | | (x)(x+2)(2)=70 | | 6x-4=149-11x | | I=f-(IR) | | -(7xy-10)+2(5xy+7)= |